2020
DOI: 10.1002/mrc.4971
|View full text |Cite|
|
Sign up to set email alerts
|

Simultaneous determination of artemisinin and its analogs and flavonoids in Artemisia annua crude extracts with the use of NMR spectroscopy

Abstract: Artemisia annua is a promising and potent antimalarial herbal drug. This activity has been ascribed to its component artemisinin, a sesquiterpene lactone. The ability to determine artemisinin and its known analogs in plant extracts is an especially difficult task because the compounds are present in low concentrations, are thermolabile, and lack ultraviolet or fluorescent chromophores. We report herein a facile and rapid 1-D 1 H, 1-D total correlation spectroscopy, 2-D 1 H-13 C heteronuclear single quantum coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Thus, based on the results of this study, we preliminarily speculated that AAE could reduce the content and gene expression level of IL-1β and IL-6 in the intestinal mucosa of broilers by regulating the TLR4/NF-κB signaling pathway. The reason might be that A. annua aqueous extract contains bioactive components (polysaccharides, polyphenols, flavonoids) that play an immunoregulatory role (18,27), and previous studies showed that polysaccharides in Artemisia could regulate the immune function of broilers through the TLR4/NF-κB signaling pathway (39). However, the specific mechanism of dietary AAE regulating intestinal immune function of broilers needs further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, based on the results of this study, we preliminarily speculated that AAE could reduce the content and gene expression level of IL-1β and IL-6 in the intestinal mucosa of broilers by regulating the TLR4/NF-κB signaling pathway. The reason might be that A. annua aqueous extract contains bioactive components (polysaccharides, polyphenols, flavonoids) that play an immunoregulatory role (18,27), and previous studies showed that polysaccharides in Artemisia could regulate the immune function of broilers through the TLR4/NF-κB signaling pathway (39). However, the specific mechanism of dietary AAE regulating intestinal immune function of broilers needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, artemisinin, an antimalarial component of A. annua studied by Tu, has attracted wide attention worldwide (12). A. annua has multiple properties, such as anticancer (13), anti-malarial (14), anti-inflammatory (15), and antioxidant (11), which are related to its rich bioactive constituents, including polysaccharides (16), polyphenols (17), and flavonoids (18). It was reported that dietary inclusion of dried A. annua leaves was used for the coccidiosis treatment and growth advancement in broilers (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 2 and 5 had never been reported before from plants of the genus Achillea. The remaining eight compounds (Figure 2) were phenolic derivatives, identified as chlorogenic acid (10) [19], the polymethoxylated flavonols penduletin (11) [20] and artemetin (12) [21], the polymethoxylated flavones santoflavone (13) [22] and salvigenin ( 14) [23] and the flavone-C-glycosides vitexin (15) [24], isovitexin ( 16) [25], and isoschaftoside (17) [26]. Wilhelmsin (7) was isolated as an optically active colorless amorphous solid with molecular formula C19H25NO6, as determined by HR-ESIMS.…”
Section: Chemical Analysis and Structure Elucidation Of Wilhelmsin And Wilhelmsolidementioning
confidence: 99%
“…The existing methods for the characterization of flavonoids include: wave spectrometry [ 23 ], UV spectrometry [ 24 ], thin-layer chromatography [ 25 ], High-Performance Liquid Chromatography (HPLC) [ 26 ], Ultra-Performance Liquid Chromatography-Mass Spectrometry (UPLC-MS) [ 27 ], UPLC-MS combined with database method [ 28 ], HPLC-MS combined with mass spectrometry cleavage law method, etc. [ 29 ].…”
Section: Introductionmentioning
confidence: 99%